Surface Engineering of C/N/O Functionalized Materials - Zhang, Yanxiang; Zhang, Yanxiang (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book discusses the latest developments in the surface engineering of C/N/O functionalized materials, including both experimental and theoretical studies on heat treatment and surface engineering of metals, ceramics, and polymers.
English
Keywords: Research & information: general; Technology: general issues; distribution of characteristic times; electrical conductivity relaxation; surface exchange coefficient; bulk diffusion coefficient; pressureless sintering; boron carbide; transition metal oxide; multiphase ceramics; solid oxide fuel cells; oxygen reduction electrode; electrocatalytic activity; duplex surface engineering; decarburization; carburization; plasma nitriding; nitriding kinetics; proton-conducting oxide; LaNbO4; NiO; sintering; theoretical calculations; basalt fibers; composites; mechanical properties; surface engineering; polylactic acid; polyethylene glycol; electrospinning; heat-not-burn tobacco; cooling performance; TA2 alloy; cold-rolling deformation; recrystallization; low-temperature nitriding; microstructure; 3Cr13 steel; microhardness; corrosion resistance; 38CrMoAl steel; modified layer; nanomaterials; PVDF; piezoelectric performance